Legal Analysis of the Legal Basis for Mediation in Dispute Resolution Efforts in Religious Courts - Triana Apriyanita; Ahmad Deski; Marwit Irianto; Habibur Rahman; danielalfaruqi (Jurnal Ragam Pengabdian, 2026)
Mediation is an important instrument in the Indonesian judicial system, particularly in Religious Courts, as an effort to resolve disputes in line with the principles of simple, fast, and low-cost justice, reinforced by PERMA Number 1 of 2016 and updated by PERMA Number 3 of 2022, which accommodates electronic mediation in response to technological developments and post-pandemic community needs. This study aims to analyze the legal basis and effectiveness of mediation in Religious Courts by comparing the provisions in both regulations, particularly in the settlement of divorce and child support cases. The method used is normative juridical with a qualitative approach through a literature study of primary, secondary, and tertiary legal materials analyzed descriptively and qualitatively. The results of the study show that mediation has a strong legal basis and plays a role in improving efficiency and access to justice, particularly through the application of electronic mediation. However, its success rate is still influenced by the low level of good faith among the parties, the limited number of certified mediators, the dominant culture of litigation, and the readiness of technological infrastructure. Therefore, it can be concluded that optimizing mediation in Religious Courts requires improving the competence of mediators, strengthening technological facilities and infrastructure, and conducting ongoing outreach so that mediation truly becomes an effective, fair, and humane means of dispute resolution.